Understanding male victimization in sexual harassment: A gender literacy analysis of patriarchal masculinity construction - Ajrun ‘Azhim Al As’hal; Ramadhanita Mustika Sari; Mega Adjie Wikhda (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Sexual harassment is one of the negative acts that has a big impact on the victims. Not only women but men today can also become victims of sexual harassment. Even the perpetrators of sexual harassment are women. This research aims to analyze the phenomenon of sexual harassment in men. The research problem focuses on the victimization of men through sexual harassment. As well as finding out the extent of society's understanding regarding gender and sexuality literacy. Methods: This study uses a qualitative research design with an ethnographic approach to describe the life experiences of eight deliberately selected informants. Primary data obtained through purposive sampling is integrated with a critical review of relevant literature to place male victimization in the broader context of sociocultural and digital structures. Finding: The findings indicate that society still demonstrates a low level of understanding regarding gender and sexuality. This lack of awareness contributes to the normalization and trivialization of sexual harassment against men, causing many male victims to remain silent due to fear of stigma, disbelief, or ridicule. Such attitudes reflect deeply embedded patriarchal norms that hinder open discussions about men’s vulnerability and reinforce gender stereotypes that portray men as invulnerable. Conclusion: This study concludes that sexual harassment against men in cyberspace tends to be normalized and ignored due to the strong influence of patriarchal masculinity norms that demand men to always appear dominant. Novelty/Originality of this article: This study offers originality through its in-depth exploration of male victimization in sexual harassment a topic that remains underrepresented in academic discourse. By examining the social ignorance and gender bias that silence male victims, this research challenges dominant gender narratives and reveals critical gaps in public understanding of gender, sexuality, and patriarchal masculinity within both offline and digital spaces.